(untitled) (Anwer Khan Modern Medical College Journal, 2018)
Background: B-type natriuretic peptide (BNP) is a biomarker of cardiovascular disease that is common in patients with chronic kidney disease (CKD). The influence of glomerular filtration rate (GFR) on BNP in CKD may stem from failure to account fully for the effects of coexistent cardiac disease, dysfunction and volume overload. Material & Methods: This is a cross sectional descriptive type of observational study conducted by the Department of Nephrology of Anwer Khan Modern Medical College Hospital during the period of Jan 2016 to Dec 2016. Results: A total number of 71 patients were included in the study. Out of them 42(59.15%) were male and 29(40.85%) were female with a M:F of 1.45:1. The mean age of the patients was 62.54+13.92 years (Range 18- 90 years). Mean e GFR was 21.81+15.01 ml/min/1.73 body surface area, mean Serum Creatinine was 5.04+3.29 mg/dl, mean Hb% was 10.90+1.5 gm/dl and that of BNP was 1335.03+1838.43 Pg/ml and that of Ejection Fraction (EF) was 50.05+12.61%. 21.12%(15) were on Stage 3 CKD(Chronic Kidney Disease) and 33.80% (24) and 45.08%(32) were on Stage-4 and Stage-5 respectively.There was a strong and highly significant inverse association between BNP and e GFR (p<0.001), with higher BNP level observed in those with lower eGFR. BNP is directly proportional to Serum Creatinine which is significant (p<0.001). BNP rises as Serum Creatinine rises. Regarding echocardiographic changes, almost all the patients 69(97.18%) had Left ventricular hypertrophy (LVH). 24(33.80%) had Left ventricular (LV) diastolic dysfunction, 19(26.76%) had LV systolic dysfunction and dilated LV and rest of them 28(39.44%)had good biventricular function. 35 (49.29%) patients had mild pericardial effusion(PE) and 39(54.92%) had hypokinesia in different cardiac wall. Most of the patients 65(91.54%) had mild mitral regurgitation (MR), tricuspid regurgitation (TR), aortic regurgitation (AR). Conclusion: Our goal was to provide compelling evidence of the association of renal function and BNP, with the full expectation that additional prospective studies will be required to validate and better define this relationship. Ideally, clinicians need clear guidelines regarding BNP and heart failure that include consideration of eGFR. Currently most institutions, including our own, continue to use BNP cutoff diagnostic levels that have not been adjusted for eGFR. Our data emphasized that a single BNP measurement must be evaluated in conjunction with the entire clinical presentation, particularly the level of renal failure. Anwer Khan Modern Medical College Journal Vol. 9, No. 2: Jul 2018, P 85-90